Dietary Practices and Nutritional Status of Adults with Type II Diabetes Mellitus Attending Clinic at Nakuru County Referral & Teaching Hospital, Kenya - ATIENO OPIYO, Beatrice; OCHOLA, Sophie; KAMAU, Jane (African Journal of Nutrition and Dietetics, 2025)
Type II diabetes mellitus (TIIDM), is a chronic metabolic disorder characterized by hyperglycemia. Despite studies showing that nutritional status and dietary practices are significant in managing Type II diabetic adults, data on the same is scanty in Nakuru County. This study assessed the relationship between dietary practices and nutritional status among adults with type II diabetes. The study adopted a cross-sectional analytical design among 105 adults recruited by systematic and simple random sampling from a sample of about 400 adults, 99 of whom consented. The study targeted adults aged 20-70 years who had been living with diabetes for over one year. Nakuru County Referral and Teaching Hospital was selected using purposive sampling, considering its well-established diabetic clinic. A researcher-administered questionnaire was used to collect data on the demographic and socio-economic characteristics of the respondents, dietary practices, nutritional status, and fasting blood glucose. The Statistical Package for Social Sciences (SPSS) Version 20.0 was used to analyze data. The results showed the respondents' mean age was 54.77 ± 8.82 years. The majority (48.5%) of the respondents were 50-60 years old, and the majority were female (63.6%), 62.6% married, 33.3% had formal employment, and 50.5% had a monthly income ranging from Ksh 20,000- 50,000. Mean energy intake per day was 2376.4 ± 156.2 and 2265.7 ± 134.2 kcal for male and female respectively. Over half (59. 6%) of respondents reported greater frequency of food consumption from five food groups per day. Half of the respondents (59%) were overweight and obese, 68.7% had central obesity. The results from Pearson correlation coefficients showed that blood glucose levels had a strong positive correlation coefficient with energy intake (r = 0.72, P < 0.0001), number of meals (r = 0.55, P < 0.0001), dietary diversity score (r = 0.52, P < 0.0001), and nutrition status (BMI) (r = 0.57, P < 0.0001). Respondents with energy intake within recommended levels were 1.4 times more likely to have average glucose than those with excess (OR = 1.42, P<0.0001). In conclusion, high-calorie diets are linked to a greater risk of complications in TIIDM adults. Health facilities should implement wellness programs for diabetic patients which may include regular consultations with dieticians for personalized meal plans to manage blood glucose levels and associated complications.